Control Parameters for the Long-Term Tensile and Compressive Strength of Stabilized Sedimentary Silt - Wagner Teixeira; Jair Arrieta Baldovino; Ronaldo Izzo (Civil Engineering Journal, 2023)
The yellow-layer soils of the Guabirotuba formation in Brazil are problematic due to their expansive nature and low-bearing capacity. There has been little exploration into stabilizing these soils using a calcium-based binder. In addition, existing methods for dosing lime to fine and coarse-grained soils using the porosity-to-lime index (η/Liv) have primarily focused on non-optimal compaction conditions to determine the split tensile and compressive strengths and empirical relationships between both tests while ignoring the study of optimal lime-soil mixes compaction conditions. Therefore, the objective of this research is to examine the unconfined compressive (qu) and split tensile (qt) behavior of a traditional Guabirotuba yellow silt stabilized with dolomitic hydrated lime (L) under standard, intermediate, and modified effort conditions and the correlation between qu and qt. The lime-soil blends were cured for up to 180 days, and 3-9% lime percentages were used under optimum compaction conditions (maximum dry density and optimum water content). The porosity/lime index (η/Liv), a semi-empirical index, was utilized to investigate the evolution of qu and qt over the short and long term. η/Livvaried between 6-25% by volume. Furthermore, the qt/qu index was calculated to be between 0.12-0.20, depending on the curing time, independent of lime addition and compaction effort used. Equations well-suited to a power function dosing qt and qu based on curing time and η/Livindex was proposed. Finally, some dosages of soil-lime mixtures were proposed for possible applications in geotechnical engineering, applying the porosity and volumetric binder index in optimal compaction conditions, which had not been applied before for lime-improved soils. Doi: 10.28991/CEJ-2023-09-04-03 Full Text: PDF